Setback or Blessing in Disguise? Implementing Management Information Systems in Partner Banks and Leasing Companies - Umarov, Umedjan; Luternauer, Patrick (World Bank, Washington, DC, 2012)
This paper intends to share the experience gained by the International Finance Corporations (IFC) Leasing Advisory Project in Central Asia and Azerbaijan (ACALF) in working with a number of financial institutions that provide leasing services. In particular, ACALF has been involved in the delivery of new management information systems (MISs) and updating existing ones at 13 institutions in 4 countries. This paper will share some of the challenges that the team faced, and the lessons learned: the need to segment the partners involved in the project; the benefits of hiring an external consultant to help implement these systems; and introducing financial incentives to spur changes.